Multi level marketing / Fatin Nadirah Abd Haris … [et al.] - Abd Haris, Fatin Nadirah; Bahar, Nursyazwana; Mohd Saad, Siti Nurfatihah; Shukri Rradzi, Ummu Marjan Izzati; Zamri, Nurin Athirah (2023)
Today, Multi-Level Marketing (MLM) is expanding into more and more fields. The insurance industry is merely one among them. Traditionally, selling insurance is viewed as a tedious and demotivating job. Well, not until you learn how MLM can increase policy sales. Companies are searching for creative ways to spread the word and attract the most business in the shortest amount of time as the insurance industry faces increasing competition (Rekha Choudhary, 2013). Multi-level marketing is a type of marketing strategy that encourages users to spread the word about a specific product across their social networks. Although this strategy was around in some capacity long before the Internet era (the famed Pyramid scheme, which has been around for at least a century, is actually a special type of multi-level marketing), its popularity is growing as a result of the accessibility of contemporary social networks (Yuval Emek, 2011 ).